“On paper it is nice, but in practice…” Analyzing the care network for drug users in policies and normative instruments of the area - Costa, Pedro Henrique Antunes da; Ronzani, Telmo Mota; Colugnati, Fernando Antonio Basile (Saúde e Sociedade, 2017)
This study aimed to understand how care networks for drug users are presented in current Brazilian drug policies. It is a documentary research with qualitative approach, and the results were grouped into three categories: general characterization of care network for drug users; network components; and care model. In general, the analyzed documents express that the networks must be constituted by different levels and devices, diversifying strategies and modalities of care and seeking the establishment of integrality, according to sociocultural and people’s characteristics. However, contradictions were observed regarding care models, connection between different sectors, relationship between State, third sector and private initiatives, and conceptions about certain services. In this sense, it is necessary to think of using such documents in a critical way with the purpose of absorbing difficulties that still exist for their effective realization, which means a constant exercise of action and reflection, even rethinking the interrelationships between paper and practice.